The effect of Euphorbia milii tea and its combination with Propolis on number of glomeruli in M.tb-infected mice: a histopathology study - Ruthirar Kalaichelvam; Ni Made Linawati; I Gusti Nyoman Sri Wiryawan; Gede Wirata; I Gusti Ayu Dewi Ratnayanti; I Wayan Sugiritama; Ida Ayu Ika Wahyuniari; I Gusti Kamasan Nyoman Arijana (DiscoverSys Inc., 2019)
Background: The role of both Euphorbia milii and Propolis is to increase the effectiveness in pathological condition of the body part damaged, include renal function in maintaining the homeostasis. That combination into mice which are infected by Mycobacterium tuberculosis will change the total number of glomerulus in the kidney.Aim: The study aims to determine the effect of combination tea from Euphorbia milii and Propolis on the number of the glomerulus in mice infected by M. tb.Method: This study confirmed randomized post-test only control group design consisting of 24 mice divided into six groups (G1-G6). E. milli flowers are obtained from flower plantations, in Ketewel, Gianyar, Bali Province took in fresh and dark red sampling. M. tuberculosis used H37Rv strain (ATCC27294) grown on Middlebrook 7H9 liquid medium for two weeks.Result: It was found that Group 3 and Group 5 from the treatment group has the most significant average number of glomerulus which was 13, followed by Group 2 and Group 6 from the control group has the largest average number of glomerulus which was 12. The differences were not significant between groups with P = 0.463 (P <0.05).Conclusion: The Euphorbia milii tea and its combination with Propolis does not affect histological change on the total number of glomerulus in mice infected with M. tb.